2023
DOI: 10.1002/glia.24379
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of the phagocytic dynamics underlying efficient clearance of adult‐born hippocampal granule cells by ramified microglia

Abstract: The phagocytosis of dead cells by microglia is essential in brain development and homeostasis. However, the mechanism underlying the efficient removal of cell corpses by ramified microglia remains poorly understood. Here, we investigated the phagocytosis of dead cells by ramified microglia in the hippocampal dentate gyrus, where adult neurogenesis and homeostatic cell clearance occur. Two-color imaging of microglia and apoptotic newborn neurons revealed two important characteristics.Firstly, frequent environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Cdk1-mediated microtubule remodeling has also recently been shown to be required for efficient cytokine trafficking and release and transformation of microglia from ramified to ameboid forms after LPS exposure in vitro and in situ ( Adrian et al, 2023 ). In contrast, findings from other studies display a reverse relationship, where ramified microglia have been shown to phagocytose synapses during adult neurogenesis ( Sierra et al, 2010 ; Kamei and Okabe, 2023 ), and ameboid microglia show reduced phagocytic capabilities in epilepsy ( Abiega et al, 2016 ; Paolicelli et al, 2022 ). The relationship between form and function is clearly not as dichotomous as historically thought, and there has been an increasing effort in the field to move away from dualistic classification of microglial function and toward a clearer understanding and appreciation of the heterogeneous states of microglia ( Dubbelaar et al, 2018 ; Paolicelli et al, 2022 ).…”
Section: Introductionmentioning
confidence: 75%
“…Cdk1-mediated microtubule remodeling has also recently been shown to be required for efficient cytokine trafficking and release and transformation of microglia from ramified to ameboid forms after LPS exposure in vitro and in situ ( Adrian et al, 2023 ). In contrast, findings from other studies display a reverse relationship, where ramified microglia have been shown to phagocytose synapses during adult neurogenesis ( Sierra et al, 2010 ; Kamei and Okabe, 2023 ), and ameboid microglia show reduced phagocytic capabilities in epilepsy ( Abiega et al, 2016 ; Paolicelli et al, 2022 ). The relationship between form and function is clearly not as dichotomous as historically thought, and there has been an increasing effort in the field to move away from dualistic classification of microglial function and toward a clearer understanding and appreciation of the heterogeneous states of microglia ( Dubbelaar et al, 2018 ; Paolicelli et al, 2022 ).…”
Section: Introductionmentioning
confidence: 75%
“…In the hippocampal dentate gyrus of the central nervous system (CNS), efferocytosis by ramified microglia (phagocytic cells that remove ACs and crops in the brain) balances cell death and neurogenesis to promote homeostasis and brain development, although the underlying mechanism requires further research ( 60 ). Paneth cells are pluripotent cells found in the small intestine.…”
Section: Physiological Functions Of Macrophages During Efferocytosismentioning
confidence: 99%
“…During this process, engulfment is tightly controlled by overlapping “find-me”, “eat-me”, and “dońt-eat-me” signals that ensure the fast and specific recognition of the apoptotic cargo (Mehrotra and Ravichandran, 2022). For example, under physiological conditions, they engulf the excess of newborn cells produced in neurogenic niches (Sierra et al, 2010; Diaz-Aparicio et al, 2020) and degrade them in few hours (Kamei and Okabe, 2023). However, in some pathological conditions, the signaling responsible for the coupling between apoptosis and phagocytois is disrupted and phagocytosis efficiency is lost.…”
Section: Introductionmentioning
confidence: 99%